KEPEMIMPINAN KEPALA SEKOLAH DAN DAMPAKNYA TERHDAP IKLIM MENGAJAR (Studi Kasus di SMPN 2 Kapetakan Cirebon) - Nunung Nurhayati (Gema Wiralodra, 2019)
The purpose of this research is to investigate the influence of Principal Leadership (KS), namely leadership as educator, leadership as manager, leadership as administrator, leadership as supervisor, leadership as leader, leadership as innovator, leadership as motivator (EMASLIM) on the teaching climate. The methodology used in this research is descriptive method, documentation study method, and path analysis technique. The results of the study concluded that 1) The leadership of the principal at the Cirebon Plot 2 Middle School was considered very good; This shows that principals are able to carry out their duties as Educators, Managers, Administrators, Supervisors, Leaders, Innovators, Motivators; (2) the teaching climate at the Cirebon Plot 2 Junior High School is considered very good. This shows that the principal is able to create an effective, efficient and conducive teaching climate.